2021
DOI: 10.1097/cce.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Breath-Synchronized Nebulized Surfactant in a Porcine Model of Acute Respiratory Distress Syndrome

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Results were compared with historic healthy control data ( 4 ). Surfactant was nebulized by an investigational vibrating mesh breath-actuated aerosol system (Aerogen Pharma), controlled by a flow sensor in the inspiratory limb of the ventilation circuit ( 3 ). Six patients were randomly allocated to receive three doses of 1,080 mg of Alveofact, a bovine surfactant widely used in preterm neonates ( 5 ), at T = 0, 8, and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were compared with historic healthy control data ( 4 ). Surfactant was nebulized by an investigational vibrating mesh breath-actuated aerosol system (Aerogen Pharma), controlled by a flow sensor in the inspiratory limb of the ventilation circuit ( 3 ). Six patients were randomly allocated to receive three doses of 1,080 mg of Alveofact, a bovine surfactant widely used in preterm neonates ( 5 ), at T = 0, 8, and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical trials of surfactant for COVID-19 ARDS are ongoing, but there is a critical need to optimize dose concentration, dose frequency and duration, and mode of delivery of therapeutic surfactant administration. In this pilot study, we evaluated the effectiveness of a prototype breath-synchronized vibrating mesh nebulizer to deliver exogenous surfactant to patients ventilated for severe COVID-19 infection ( 2 , 3 ) and report here endogenous surfactant status, turnover, and half-life of administered surfactant. These results have not been previously reported in abstract form.…”
mentioning
confidence: 99%
“…This has led to a shift away from jet nebulizers to VMNs in animal and clinical studies ( Tables 1 , 2 ). Synchronization of aerosol delivery and spontaneous respiration can further enhance lung dose as recently shown in ventilated, surfactant-deficient juvenile rabbits and in a porcine ARDS model using liquid bovine surfactant and a novel breath-actuated small particle VMN with photo-defined aperture plate (PDAP) technology (Aerogen Pharma, San Mateo, CA) placed between the Y- connector of the ventilator circuit and the endotracheal tube ( 63 , 64 ). Synchronization of surfactant delivery was managed by a flow sensor in the inspiratory line of the ventilator and minimized surfactant loss during expiration.…”
Section: Nebulizationmentioning
confidence: 99%
“…We included a limited number of controls (n = 2) to provide descriptive data to show rate of endogenous surfactant repletion and recovery against treatment groups. Unlike other studies [23,36], that also showed lavage maintains surfactant-deficiency over several hours of continued ventilator support, Controls were underpowered to do a comparative statistical analysis with treatment groups. Additionally, since these animals were relatively small, sedated, and had severe lung disease, it is difficult to extrapolate from these animal findings to human pre-term newborns with RDS, especially if they are larger, have a milder form of lung disease, or are not sedated.…”
Section: Limitationsmentioning
confidence: 99%